PENGARUH STRATEGI DIRECT MARKETING DAN ADVERTISING TERHADAP KEPUTUSAN MEMBELI DI PERUSAHAAN SHOPIE PARIS SAMARINDA - -, Yenita Pebrina (EKONOMIA, 2019)
Based on the formulation of the problem, the objectives obtained are as follows: a) To determine the effect of direct marketing has an influence or not on the decision to buy Shopie Paris in Samarinda. b) To determine the influence of advertising strategy has an influence or not on the decision to buy Shopie Paris in SamarindaThe problems contained in this are as follows: 1) Does the direct marketing strategy have an influence on buying decisions at Paris Shopie Companies in Samarinda? 2) Does the advertising strategy have an influence on buying decisions at Paris Shopie Companies in Samarinda? 3) Does the advertising and direct marketing strategy together have an influence on buying decisions at the Shopie Paris Company in Samarinda?The analytical tool used to analyze uses multiple linear regression analysis. The results of the analysis stated: a) The results of the t test showed that the Direct Marketing variable (X1) had a t count of 2,883> from the t table of 1.98498 with a significant level of 0.005 <0.05 which means that the Direct Marketing (X1) variable had a significant effect on the Buying Decision and it can be seen that the relationship between the Direct Marketing (X1) variable to the Buying Decision (Y) is 0.281. b) The result of the t test shows that the Advertising (X2) variable has a t count of 5.104> from t table of 1.98498 with a significant level of 0.000 <0.05 which means that the Advertising variable (X2) has a significant effect on the Buying Decision and the variable relationship can be known Advertising (X2) on Buying Decision (Y) is equal to 0.460.